2007
DOI: 10.1016/j.jalgebra.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Crossed product conditions for central simple algebras in terms of irreducible subgroups

Abstract: Let M m (D) be a finite dimensional F -central simple algebra. It is shown that M m (D) is a crossed product over a maximal subfield if and only if GL m (D) has an irreducible subgroup G containing a normal abelian subgroup A such that C G (A) = A and F [A] contains no zero divisor. Various other crossed product conditions on subgroups of D * are also investigated. In particular, it is shown that if D * contains either an irreducible finite subgroup or an irreducible soluble-by-finite subgroup that contains no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…From Lemma 2.18, it follows that D is a crossed product of Here, we should point out that the above results concerning the structure of soluble-byfinite subgroups of division algebras were nicely obtained by Wehrfritz for the soluble-byfinite subgroups of GL n (D), where D is a division algebra in [107]. His results demonstrates that if G is a soluble-by-finite subgroup of GL n (D), then G has an abelian normal subgroup of finite index dividing b(n) deg(D) 2n , where b(n) is an integer valued function which depends only on n. By an interesting result of [45], the existence of a finite absolutely irreducible subgroup in a division algebra D guarantees that D is a crossed product division algebra. Here, we give a very short proof for this fact.…”
Section: Soluble-by-finite Subgroups Of Division Algebrasmentioning
confidence: 92%
See 1 more Smart Citation
“…From Lemma 2.18, it follows that D is a crossed product of Here, we should point out that the above results concerning the structure of soluble-byfinite subgroups of division algebras were nicely obtained by Wehrfritz for the soluble-byfinite subgroups of GL n (D), where D is a division algebra in [107]. His results demonstrates that if G is a soluble-by-finite subgroup of GL n (D), then G has an abelian normal subgroup of finite index dividing b(n) deg(D) 2n , where b(n) is an integer valued function which depends only on n. By an interesting result of [45], the existence of a finite absolutely irreducible subgroup in a division algebra D guarantees that D is a crossed product division algebra. Here, we give a very short proof for this fact.…”
Section: Soluble-by-finite Subgroups Of Division Algebrasmentioning
confidence: 92%
“…The first significant result concerning Question 2.5, was obtained in [60] where the author showed that if G is a soluble maximal subgroup (this means that G is a maximal subgroup of D * that is soluble), then the question has a positive answer. Afterwards, this question became the subject of a series of papers including [13], [14], [47] and [45]. In [13], it was proved that if G is soluble, then D is a quasi-crossed product division algebra in the sense that it contains a tower of subfields F = Z(D) K ⊆ L such that K/F is Galois, L is a maximal subfield and L/K is an abelian Galois extension.…”
Section: Theorem 24 ([69]mentioning
confidence: 99%